Impact of NGO market based approaches on food security in high density urban areas: case of Epworth - Sigodo, Chipo (BUSE, 2024)
This study evaluates the impact of NGO market-based programs on food security among households in Epworth, a high-density urban area. Employing a mixed-methods approach, the research integrates quantitative data from structured surveys with qualitative insights from in-depth interviews. The study involved a sample of 120 households selected using stratified random sampling to ensure representation across different demographic segments. Quantitative analysis revealed significant improvements in food security indicators among households participating in NGO programs. Regression analysis highlighted that program type, household income, duration of participation, education level, and access to markets positively influenced the Food Security Index. Conversely, larger household size was associated with lower food security levels. These findings align with theoretical perspectives on the importance of economic resources, education, and inclusive development strategies in achieving food security. Qualitative data provided additional context, illustrating specific benefits and challenges associated with NGO interventions. Participants reported improved access to credit, enhanced agricultural skills, and increased food availability as key strengths of the programs. However, challenges such as limited coverage, inadequate funding, and cultural barriers were also identified, suggesting areas where program effectiveness could be improved. The study concludes that NGO market-based programs positively impact food security in Epworth. However, effectiveness varies based on program type, duration of participation, and household characteristics. The research underscores the need for tailored and inclusive interventions to address specific vulnerabilities and enhance program outcomes. Policy implications include expanding program coverage, increasing funding, addressing cultural barriers, enhancing gender inclusivity, focusing on education and training, and ensuring sustainable long-term support. The study recommends further research on the long-term impacts of NGO programs, comparative analysis across different contexts, gender-specific challenges, and cultural adaptation of programs.
Keywords: NGO market-based approaches; Food security